Specyfika pracy nauczyciela z zespołem wokalnym = The specificity of the teacher`s work with the vocal ensemble - Jatczak, Anita (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article focuses on the data connected with the singing process. The singing process is presented as the most attractive form of musical performance also presents. It the issue of possitive effects of the singing influence on children health and education.
Keywords: zespół wokalny; edukacja artystyczna; edukacja muzyczna; vocal ensemble; art education; music education